2011
DOI: 10.1089/apc.2010.0365
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Pneumonia Severity in HIV-Infected Adults Admitted to an Urban Public Hospital

Abstract: Data on outcomes of community-acquired pneumonia (CAP) in the HIV-infected population are mixed and the perception of worse outcomes in HIV may lead to excess hospitalization. We retrospectively evaluated the utility of the Pneumonia Severity Index, or PORT score, as a prediction rule for mortality in 102 HIV-infected adults hospitalized at an urban public hospital with CAP. Primary outcome was survival at 30 days. Secondary outcomes included survival on discharge, intensive care unit (ICU) admission, length o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 26 publications
0
22
0
3
Order By: Relevance
“…The pneumonia severity index (PSI) has been extensively validated, including in HIV+ populations with risk groups predictive of pneumonia-related mortality [1722]. All variables contributing to the PSI were obtained at the time of presentation.…”
Section: Methodsmentioning
confidence: 99%
“…The pneumonia severity index (PSI) has been extensively validated, including in HIV+ populations with risk groups predictive of pneumonia-related mortality [1722]. All variables contributing to the PSI were obtained at the time of presentation.…”
Section: Methodsmentioning
confidence: 99%
“…28 Stemming from different methodologies, there is disagreement in the association between lower CD4 cell counts and worse outcomes, including multilobar consolidation, longer time to clinical stability and increased mortality. Some studies have reported no impact of this marker on CAP outcome, 11,17 whereas others have conversely found a significant impact on mortality, prompting authors to recommend admission of all patients in the <200 cells/mL subgroup. 13,15,29 Taking into account our results, in addition to CURB-65 scores, low CD4 cell counts seem to be independent predictive factors in the severity assessment of HIV-positive patients presenting with CAP.…”
Section: Discussionmentioning
confidence: 99%
“…6,12,[14][15][16] Research has addressed this topic since the beginning of the HAART era, focusing on the course and outcome of CAP in HIV-positive patients. 5,13,15,[17][18][19] HIV infection is a known risk factor for bacteraemia, 5,19 but apparently not for higher mortality 5,18,20,21 or time to clinical stability. 20,21 Evidence on prediction of severity and resulting guidance on risk stratification and related management remains heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Такая ситуация объясняется тем, что заболеваемость ВП не так сильно связана с CD4 лимфопенией. В отли чие от вторичных заболеваний, которые, как прави ло, развиваются на поздних стадиях ВИЧ инфек ции, бактериальные пневмонии могут развиться в любой период заболевания и при любом количест ве CD4 лимфоцитов [9][10][11]. Это связано с бóльшей значимостью гуморального иммунитета по сравне нию с клеточным в борьбе с традиционными возбу дителями пневмоний.…”
Section: обзорыunclassified